ACOUSTICS BACKSCATTER MEASUREMENT OF LARGE MICROPLASTICS IN CONTROLLED CONDITIONS USING A SINGLE BEAM ECHOSOUNDER: PENGUKURAN ACOUSTICS BACKSCATTER LARGE MICROPLASTICS DALAM KONDISI TERKONTROL DENGAN ECHOSOUNDER SOROT TUNGGAL - Bimo Aji Nugroho; Henry M. Manik; Indra Jaya; Muhammad Reza Cordova (Jurnal Teknologi Perikanan dan Kelautan, 2026)
Microplastics are particles ≤ 5 mm in size that result from the physical and chemical degradation of polymer-based materials. These particles are ubiquitously distributed in aquatic environments and pose significant threats to aquatic organisms. Currently, microplastic detection predominantly relies on water-sample analyses at a particular point, a method that is inherently limited in spatial coverage. Hydroacoustic techniques offer a promising alternative for detecting microplastics within the water column over larger areas. This study aims to assess the detection of large microplastics (1–5 mm) using a single-beam echosounder (SBES), specifically the Simrad EK-15, under laboratory-controlled conditions. Data validation was performed by comparing acoustic measurements with water-sample analyses using correlation and regression methods. The results reveal high model suitability with coefficients of determination exceeding 0.8 (R² > 0.8) and strong linear correlations (r > 0.8) between the two datasets. Furthermore, the average volume backscattering coefficient (sv) for large microplastics at depths corresponding to 1.5, 1, and 0.5 m were 9.025E-05, 5.403E-05, and 6.850E-05 m²/m³, respectively, while the mean volume backscattering strength (SV) values were -40.445 dB, -42.674 dB, and -41.643 dB at these depths. These findings underscore the efficacy of the SBES in detecting microplastics sized 1–5 mm within the water column and suggest that hydroacoustic methods can serve as a viable approach for expanding microplastic monitoring capabilities.